Merchants, Traders, Entrepreneurs - Markovits, C. author. aut Link
XII, 292 p.
Keywords: This book deals with three main aspects of the history of Indian business: The relationship between business and politics, the position of merchants and businessmen in the economy and society of late colonial India, and how particular merchant networks extended the range of their operations to the entire subcontinent and the wider world.